2020
DOI: 10.1097/iae.0000000000002641
|View full text |Cite
|
Sign up to set email alerts
|

Characterization by Fractal Dimension Analysis of the Retinal Capillary Network in Parkinson Disease

Abstract: Purpose: To characterize retinal capillary complexity by optical coherence tomography angiography in Parkinson disease. Method: Twenty-five Parkinson disease patients and 25 age- and gender-matched healthy controls were recruited. Optical coherence tomography angiography and optical coherence tomography imaged the superficial and deep retinal capillary plexuses and retinal structure. Retinal capillary skeleton density, retinal capillary perfusion densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 30 publications
7
42
1
2
Order By: Relevance
“…Research by Shi et al, unique in its position addressing retinal microvascular changes in PD and one of two studies using OCT-A, showed that FD of the superficial vascular plexus was decreased in all analyzed regions and that FD of the deep vascular plexus was decreased in all but two ROIs. Of note, this was the only study able to confirm a significant correlation with disease duration (Shi et al, 2019). Table 3 summarizes the findings on fractal dimension analysis of the retinal vasculature in stroke patients.…”
Section: Outcomes Of Fractal Analysis In Studies On Neurodegenerativementioning
confidence: 79%
See 1 more Smart Citation
“…Research by Shi et al, unique in its position addressing retinal microvascular changes in PD and one of two studies using OCT-A, showed that FD of the superficial vascular plexus was decreased in all analyzed regions and that FD of the deep vascular plexus was decreased in all but two ROIs. Of note, this was the only study able to confirm a significant correlation with disease duration (Shi et al, 2019). Table 3 summarizes the findings on fractal dimension analysis of the retinal vasculature in stroke patients.…”
Section: Outcomes Of Fractal Analysis In Studies On Neurodegenerativementioning
confidence: 79%
“…Patient characteristics of included studies are reported in Table 1. Subjects included in the central neurodegeneration section of this review show heterogeneity in mean age ranging from 59 (Shi et al, 2019) up to 81 (Cabrera DeBuc et al, 2018) years. In the section dedicated to studies focusing on stroke patients, the heterogeneity in mean age is even higher, from 44 (Cavallari et al, 2011) up to 74 (Kawasaki et al, 2011.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In addition to neurodegeneration, the vascular impairment has been identified as a possible key factor to the occurrence and progression of PD [ 83 ]. Recently, retinal microvessel status has been evaluated in patients with PD using OCTA [ 84 , 85 ]. Patients with early stage PD showed a reduced perfusion density of SCP in all the quadrants evaluated individually and in the total annular zone, defined as an area of 2.5 mm diameter centered on the fovea excluding the FAZ [ 84 , 85 ].…”
Section: Parkinson’s Diseasementioning
confidence: 99%
“…Recently, retinal microvessel status has been evaluated in patients with PD using OCTA [ 84 , 85 ]. Patients with early stage PD showed a reduced perfusion density of SCP in all the quadrants evaluated individually and in the total annular zone, defined as an area of 2.5 mm diameter centered on the fovea excluding the FAZ [ 84 , 85 ]. Given previous studies on animal models of PD reporting the accumulation of α-synuclein at the level of the wall of arteries, authors hypothesized that the same pathogenetic mechanism could explain the decreased perfusion density in SCP in PD patients [ 83 ].…”
Section: Parkinson’s Diseasementioning
confidence: 99%
“…OCTA provided a unique and non-invasive technique for the evaluation of blood flow and vascular density and has been applied to the prediction of disease beyond the retinal vascular disease, such as Alzheimer’s disease and Parkinson’s disease [ 15 , 16 ]. The imaging study of intraocular tumors using OCTA was a new field.…”
Section: Discussionmentioning
confidence: 99%